2022
DOI: 10.1590/0102-672020220002e1714
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Versus Laparoscopic Incisional Hernia Repair: Differences in Direct Costs From a Brazilian Public Institute Perspective

Abstract: BACKGROUND: Robotic-assisted surgery research has grown dramatically in the past two decades and the advantages over traditional videolaparoscopy have been extensively debated. For hernias, the robotic system can increase intraoperative strategies, especially in complex hernias or incisional hernias. AIMS: This study aimed to compare the direct cost differences between robotic and laparoscopic hernia repair and determine each source of expenditure that may be related to the increased costs in a robotic progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…After the exclusion of duplicates and the application of inclusion and exclusion criteria, 15 RCTs were selected. The European Hernia Society and the Americas Hernia Society Guidelines and Costa et al 7 study were also included in the discussion as mentioned above 7 , 9 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the exclusion of duplicates and the application of inclusion and exclusion criteria, 15 RCTs were selected. The European Hernia Society and the Americas Hernia Society Guidelines and Costa et al 7 study were also included in the discussion as mentioned above 7 , 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Robotic-assisted surgery research has grown in the past two decades in abdominal hernias and the advantages over traditional videolaparoscopy have been debated. Costa et al analyzed the costs of a robotic program in a Brazilian public institution to treat abdominal hernias and concluded that the robotic system can increase intraoperative strategies, especially in complex hernias or incisional hernias, however, it adds a significant overall cost to traditional laparoscopic hernia repair, especially umbilical and epigastric hernias 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing popularity of minimally invasive approaches in abdominal surgery, it is unlikely that the open approach will ever entirely disappear from the surgical landscape. Minimally invasive techniques, such as laparoscopy and robotic-assisted surgery, have indeed revolutionized many procedures, offering benefits such as less pain, shorter hospital stays, and faster recovery times 6 , 7 , 10 , 12 , 24 , 29 . However, the open approach continues to hold a crucial role, particularly in challenging cases that demand wide exposure.…”
Section: Introductionmentioning
confidence: 99%
“…With its unique features, including 3D imaging, a mechanical arm with 7 degrees of freedom, tremor filtration, and more ergonomic design, da Vinci surgery has elevated surgical precision to unprecedented heights and ushered minimally invasive surgery into a new era [7,8]. Currently, it has been successfully applied in abdominal wall incisional hernia repair, paraesophageal hernia repair, and inguinal hernia repair, demonstrating its technical advantages [9][10][11]. While several randomized controlled studies and nonrandomized controlled studies have compared RTAPP with LTAPP in the treatment of inguinal hernia [12][13][14][15][16][17][18][19][20][21], there is limited data from single-center studies, and clinical reports yield inconsistent results.…”
Section: Introductionmentioning
confidence: 99%